Sleep following traumatic brain injury (TBI): experiences and influencing factors. (6th December 2019) - Mumbower, Rachael; Childs, Gwendolyn; Vance, David E.; Dreer, Laura E.; Novack, Thomas; Heaton, Karen
ABSTRACT: Objective : This study aimed to 1) describe and explore the experiences of sleep following a moderate or severe traumatic brain injury (TBI) in community-dwelling adults, 2) elicit factors that positively or negatively impact the sleep experience, and 3) understand sleep-related education provided to survivors. Design : Qualitative description. Methods : Face-to-face interviews with 16 individuals using a semi-structured interview guide. Transcripts were systematically coded and common themes were identified. The final sample consisted of primarily Caucasian men with average age of 32.4 years (SD = 9.9), and average of 2.6 years (SD = .89) years post injury. Results : Community-dwelling survivors of TBI experienced poor sleep quality and quantity post-injury and described a variety of approaches to manage their sleep. Survivors described coping with sleep changes and using sleep as a coping mechanism for TBI. Additionally, survivors' responses indicated perceived lack of resources and preference for receiving education from knowledgeable, familiar clinicians during face-to-face encounters. Conclusions : This study provides a description of reported sleep experiences following TBI and adds new knowledge regarding sleep management strategies and preferences for resources. The findings suggest a need for education regarding sleep for rehabilitation professionals and long-term sleep support after discharge from rehabilitation.